Effectiveness of nicotine-based and non-nicotine based drug delivery system for smoking cessation among the elderly - Mat Husin, Amri Nurhakim; Azmi, Nurul Atifah; Mohd Sabari, Nurul Hanis; Nik Mohamed, Mohamad Haniki; Mohammad Hamdi, Nurul Ain; Haris @ Harith, Muhammad Salahuddin (UPM Press, 2022)
Smoking is associated with a higher risk of mortality, especially in smokers with cardiovascular and respiratory diseases. Smoking cessation remains the most effective approach in reducing smoking-related illness risks at all ages. For elderly smokers, smoking cessation has been proved to prolong life expectancy and reduce the risk of stroke and ischemic heart disease. However, a wide selection of smoking cessation medications makes prescribing challenging, especially among elderly smokers. Inability to recommend the best treatment may reduce the smoking cessation success rate in the elderly. Therefore, this study compares the effectiveness of pharmacotherapy available and correlate the effect of ageing on the effectiveness, leading to the recommendation of the best medication for elderly smokers. A systematic searching strategy was performed in three different databases by using predetermined search strings. Overall, this systematic review revealed that varenicline showed the greatest smoking cessation rate among the elderly, followed by bupropion and NRT.